Expression of DNA methyltransferases in adult dorsal root ganglia is cell-type specific and up regulated in a rodent model of neuropathic pain - Pollema-Mays, Sarah L.; Centeno, Maria V.; Apkarian, A. V.; Martina, Marco (Frontiers in Cellular Neuroscience, 2014)
Neuropathic pain is associated with hyperexcitability and intrinsic firing of dorsal root ganglia (DRG) neurons. These phenotypical changes can be long lasting, potentially spanning the entire life of animal models, and depend on altered expression of numerous proteins, including many ion channels. Yet, how DRGs maintain long-term changes in protein expression in neuropathic conditions remains unclear. DNA methylation is a well-known mechanism of epigenetic control of gene expression and is achieved by the action of three enzymes: DNA methyltransferase (DNMT) 1, 3a, and 3b, which have been studied primarily during development. We first performed immunohistochemical analysis to assess whether these enzymes are expressed in adult rat DRGs (L4–5) and found that DNMT1 is expressed in both glia and neurons, DNMT3a is preferentially expressed in glia and DNMT3b is preferentially expressed in neurons. A rat model of neuropathic pain was then used to determine whether nerve injury may induce epigenetic changes in DRGs at multiple time points after pain onset. Real-time RT PCR analysis revealed robust and time-dependent changes in DNMT transcript expression in ipsilateral DRGs from spared nerve injury (SNI) but not sham rats. Interestingly, DNMT3b transcript showed a robust upregulation that appeared already 1 week after surgery and persisted at 4 weeks (our endpoint); in contrast, DNMT1 and DNMT3a transcripts showed only moderate upregulation that was transient and did not appear until the second week. We suggest that DNMT regulation in adult DRGs may be a contributor to the pain phenotype and merits further study.